Common sense storage : clever solutions for an organized life . - Creative Publishing International (Minneapolis, Minn. : Creative Pub. International, 2010)
"Inspirational photos and concise, practical information on how to achieve an organized home"--Provided by publisher.
Getting organized -- Kitchens & pantries -- Bathrooms, linens & laundry -- Family & entertainment rooms -- Bedrooms -- Home offices -- Attics & basements -- Garages -- Resource guide.
Keywords: Storage in the home